Identification of Substances in the Essential Oil and Antibacterial Activities of Heptaptera anisoptera (DC.) Turin (Institue of Medicinal Plants, ACECR, 2011)
Background: Heptaptera anisoptera from Umbelliferae was growth in some spaces of Iran. Some researches have been carried out on the herb about isolation and structure elucidation of some phytochemicals. There isn't any report about identification of substances in the essential oil and antibacterial activities of this plant. Objectives: Identification of substances in the essential oil and antibacterial activities of Heptaptera anisoptera (DC.) Turin. Literature survey has shown that the herb has not previously been investigated for essential oil and antibacterial activities. Methods: The essential oil of aerial parts from Heptaptera anisoptera (DC) Turin. (Umbelliferae) was obtained by hydrodistillation. The oil was analyzed by GC/MS. The effects of methanol, chloroform and hexane extracts of this plant were tested on 10 G+ and G- bacteria in different dilutions. Results: 91.3% of the oil (10 components) was identified. Method of identification was based on comparison of the mass spectra and retention indices of the components with standards. Thymol (48.8%), 3-carene (17.6%), phytol (7.9%), methyl linolenate (5.6%), and methyl palmitate (4.7%) were the major components. None of the extracts are any effect on tested bacteria. Conclusion: While thymol is the major component of some herbs such as thymes and ajowan, other plants can have thymol as major component. In the oil of thymes, carvacrol is reported, too, but it didn't identify in the oil of H. anisoptera. Similar to other essential oils, monoterpenoides were major compounds. As a result of use of long time for oil extraction (3 hours), non-terpenoides components (diterpenoide, fatty acids and esters) came in the oil, too. Despite the fact of antibacterial activity of plants, none extract of H. anisoptera in 4 test models, have significant antibacterial effect.